Implementation of support meetings for patients undergoing outpatient chemotherapy by a multidisciplinary cancer team - Miho Jinno; Misako Dai; Kaori Ito; Yosuke Ando; Seira Toyosato-Nishibe; Maki Akiyoshi; Sachie Noda; Hidezo Matsuda; Naho Tsujii; Miho Zennami; Masami Yamamura; Yoko Katagata; et al. (Fujita Medical Journal)
Background: Outpatient chemotherapy is a standard treatment for cancer. In nursing care for outpatients, it is important to enhance patients’ self-efficacy. Vicarious experiences that can be gained through interactions with other patients with cancer can be useful for achieving this. While inpatients can gain vicarious experiences through their hospital stay, outpatients typically have fewer opportunities to do so. Aims: This report aimed to examine the results of implementation of support meetings for patients receiving outpatient chemotherapy. Methods: Starting in April 2019, support meetings were held once a month for outpatients on Thursdays from 14:00 to 16:00 in a hospital conference room. Medical professionals designed the programme of support meetings to allow patients to interact with each other and engage in vicarious experiences. At each meeting, satisfaction regarding the support meeting content was evaluated by self-administered questionnaire. Moreover, the nurse asked all participants to talk about their interactions, and recorded and extracted narratives about vicarious experiences. Findings: The 32 participants had a median age (interquartile range) of 63.5 years (55–70 years). There were 26 females (81.2%). The median satisfaction scores ranged from 2.9 to 4 for the content of each meeting. Patients talked about the value of learning from the experiences of other patients and the easing of loneliness. Conclusion: The results suggested that support meetings can provide vicarious experiences for patients receiving outpatient chemotherapy.